PENGARUH KUALITAS PELAYANAN SEKOLAH TERHADAP KEPUASAN SISWA SMA NEGERI 1 SUMBERLAWANG KABUPATEN SRAGEN TAHUN 2015/2016 - Anggraini, Melisa Dwi; Wahyuni, Sri; Totalia, Salman Alfarisy (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2016)
The objective of research were to find out the effect of sevice quality school (reliability, assurance, tangible, empathy and responsivines)to student satisfaction SMA Negeri 1 Sumberlawang Sragen 2015/2016 simultaneosly and partially. Reply method used in this research is descriptive quantitative. Sample in this research is 100 student of class X and XI SMA Negeri 1 Sumberlawang Sragen.The data collection techniques used questionnaires. The data were analyzed by  using  multiple regression analysis.The results showed that there is significant influence simultaneously and partially between service quality school (reliability, assurance, tangible, empathy and responsivines) to student satisfaction SMA Negeri 1 Sumberlawang Sragen 2015/2016. The influence of the variable sevice quality to student satisfaction obtained from the calculation of adjusted r square of 86,9%. The influence of the variable reliability 0,0173, assurance 0,087, tangible 0,512, empathy 0,102 dan responsivines 0,286 derived from the value coefficients. Impact of service quality on student satisfaction is the variable most tangible at 0,512 and influence the weakest assurance at 0,087.